COST-EFFECTIVENESS OF ALTERNATIVE APPROACHES IN THE MANAGEMENT OF DYSPEPSIA - Makris, Nicholaos; Barkun, Alan; Crott, Ralph; Fallone, Carlo A. (International journal of technology assessment in health care, 2003)
Objectives: To assess the cost-effectiveness of alternative initial strategies in the management of uninvestigated dyspepsia in adult patients presenting to a primary care physician in Canada. Methods: Clinical decision-making was modeled based on outcomes data from the literature and expert opinion. Costs were obtained from official reimbursement lists, and a detailed microcosting analysis of a gastroscopy. Costs were analysed over a one-year period after initial presentation, including consideration of a single relapse of symptoms. The main outcome was a symptomatic cure. The seven management strategies based on different initial tests were endoscopy, double-contrast barium meal, empirical eradication therapy, empirical antisecretory treatment, urea breath test (UBT), laboratory serology, and sequential testing (laboratory serology followed, if Helicobacter pylori positive, by UBT). Results: In patients under age 45, endoscopy, double-contrast barium meal, and sequential testing were not cost-effective approaches. UBT was the most effective and most costly strategy costing $8,238 per additional patient cure compared with laboratory serology. In patients over age 45, UBT was again the most effective and most costly strategy, but endoscopy was the most reliable in detecting gastric cancers. Clinical variables that impacted these findings were the probability of symptomatic relapse in patients with nonulcer dyspepsia (NUD) after successful versus failed H. pylori eradication, the probability of finding a duodenal ulcer (DU) in a young dyspeptic patient, the specificity of UBT, and the prevalence of H. pylori in patients with DU. Conclusions: A “test-and-treat” approach was favored, with UBT being the most effective but most costly initial test in adult dyspeptics under age 45. The choice of the most cost-effective approach is dependent on the benefits of H. pylori eradication in patients with NUD. In patients over age 45, UBT is the most effective and most costly, but endoscopy results in the early detection of most gastric cancers.The authors are indebted to the other members of the UBTAN Group, including Drs. Phil Sherman, Alan Thomson, and Sander Veldhuyzen van Zanten. The authors also thank Paul Sinclair, Eileen Grace, and Lawrence Joseph for their much valued comments and opinions. AB and CAF are research scholars of the Fonds de la Recherche en Santé du Québec. This work was supported in part by an “at arms length” grant from AstraZeneca Canada.